Acute toxicity and gene responses induced by endosulfan in zebrafish (Danio rerio) embryos. Issue 1 (1st October 2016) - Moon, Young-Sun; Jeon, Hwang-Ju; Nam, Tae-Hoon; Choi, Sung-Deuk; Park, Byung-Jun; Ok, Yong Sik; Lee, Sung-Eun
Abstract: Endosulfan has been listed as a persistent organic pollutant, and is frequently found in agricultural environments during monitoring processes owing to its heavy use and persistent characteristics. This study was conducted to understand the effects of endosulfan on the development of zebrafish ( Danio rerio ) embryos by exposing them to a specific range of endosulfan concentrations. Exposing zebrafish embryos to endosulfan for 96 h yielded no acute toxicity until the concentration reached 1500 μg L −1, whereas malformed zebrafish larvae developed severely curved spines and shortened tails. About 50% of zebrafish larvae were malformed when exposed to 600 μg L −1 of endosulfan. Comparative gene expression using real-time quantitative polymerase chain reaction was assessed using endosulfan-exposed zebrafish embryos. CYP1A and CYP3A were significantly enhanced in response to endosulfan treatment. Two genes, acacb and fasn, encoding acetyl-CoA carboxylase b and fatty acid synthase proteins, respectively, were also up-regulated after treating zebrafish embryos with endosulfan. These genes are also involved in fatty acid biosynthesis. The genes encoding vitellogenin and Hsp70 increased in a concentration-dependent manner in embryos. Finally, biochemical studies showed that acetylcholinesterase activity was reduced, whereas glutathione S -transferase and carboxylesterase activities were enhanced in zebrafish embryos after endosulfan treatment. These biochemical and molecular biological differences might be used for tools to determine contamination of endosulfan in the aquatic environment.